Komunikasi Interpersonal Siswa Pengguna Internet dan Implikasinya terhadap Layanan Bimbingan dan Konseling - Winda Marnita; Riska Ahmad; Azrul Said (Indonesian Institute for Counseling, Education and Therapy (IICET), 2014)
Interpersonal communication through the internet is now becoming a trend among the public, especially students. Online communication is of interest by students because it is cheap, easy and fast. The Internet as a communication medium between the interpersonal students with parents, teachers and fellow internet users. The use of the internet as a medium of interpersonal communication understood the students well. Aspects that should be understood in communicating interpersonal are students use of the internet, the purpose of the use of the internet, openness, attention, empathy, equality. This research is descriptive research, the population in this study are students of SMP Negeri Padang 25 that become the subject of research is as much as 69 students, data collected by using question form. This study reveals students' interpersonal communication through the internet and the implications for guidance and counselling services. Because most of students have yet to understand and implement the aspects of the accommodation.